Studying the side effects of alcoholic extract of dill leaves on the sperm of laboratory mice (Mus musculus) (Journal of the College of Basic Education, 2023)
Dill is an annual plant of the Anethum graveolens family used in spices, which include anise, parsley, caraway, coriander, cumin, and fennel. However, it resembles these plants to fennel in terms of taste, shape of leaves, seeds and flavor, and that is why they called it false fennel, and its names include snot, moss, and rover. Turkey is its original homeland, and its cultivation has spread in ancient times in Greece. Dill seeds and its brown fruits have five long veins and the aromatic taste is in the green leaves and seeds, but the seeds are more used for commercial purposes and marketing as spices. The leaves are eaten raw or added to salads or cooked with soups and soups ( 2). And for its popular use in some countries. In Iraq, seeds and leaves are used, and the latter is popular with people. The dill fruits contain multiple effective components, the most important of which is the volatile oil called dill oil, which is found at a rate ranging between (3-4)% of the weight of the fruits, and it is similar to caraway oil and the most important Its components are carvone, which constitutes more than half of the amount of oil. The oil also contains limonene and phelandrine (3). Dill oil is light yellow in color and smells fragrant. For use with a distinctive smell. The seeds contain sticky mucus, resinous substances (gum) and nitrogenous substances. These seeds contain components and materials that are resistant to cancerous tumors (4). Dill was prescribed for the treatment of diseases in the past. Useful in spasm of the diaphragm, and its ashes (after burning) are useful in bandaging wounds, and it is a diuretic and a diuretic for lactating women, when cooked with soup. Sheikh Ibn Sina described it as hypnotic and useful in treating hemorrhoids (5). Recently, "dill has many uses, and it is known." Dill leaves are rich in vitamin A in the form of carotenoids and vitamin C. Rather, they are compared to the very rich food sources of these two vitamins, and both vitamins are antioxidant vitamins. The leaves also contain dietary fiber that stimulates the intestines and regulates oxidation. The leaves also contain invigorating dietary fiber For the intestines and the organization for the absorption of fats and simple sugars and reduce the absorption of cholesterol and salts of the gallbladder. In addition to its good flavor and opening the appetite, the seeds contain a good content of protein, fats and dietary fiber. They are particularly rich in iron. D, calcium, potassium, a group of B vitamins, vitamin K, and seeds are available at apothecaries who prescribe them for the purposes mentioned above, and the modern supermarket is not without them (6). It should be noted that the conditions for dill germination and cultivation are available and easy, and it can be grown in the home garden.